Jumlah Ternak Sapi Potong yang Dijual dan Biaya Pakan Memengaruhi Pendapatan Tunai Peternak di Kawasan Amfuang Kabupaten Kupang - Sol'uf, Morin Mediviani; Krova, Maria; Makandolu, Solvi Mariana (Jurnal Veteriner; Vol 23 No 2 (2022)DO - 10.19087/jveteriner.2022.23.2.195, 2022)
A study was conducted in the Amfoang Region, Kupang Regency with the aim of knowing the amount of cash income and the factors that influence the cash income of beef cattle farmers with different maintenance systems in the Amfoang  Region, Kupang Regency. Sampling is done in stages. The first and second stages, namely the determination of two sub-districts and four sample villages, were carried out purposively with the consideration that the two sub-districts and four villages had the largest and smallest beef cattle populations and represented the highlands and lowlands in the Amfoang area. The third stage is the determination of 40 non-proportional random sample farmers in each rearing system. The analytical method used is multiple linear regression. The results showed that cash income in the tie system is 61,93% higher than in the loose grazing system. In the tie system, the cash income obtained by farmers is Rp11.646.824,95 or Rp8.088.072,88 per unit of livestock. In the loose grazing system,cash income is Rp7.157.250 or Rp5.818.902,44 per unit of livestock. Factors which has a real relationship to cash income of beef cattle business both in the tie system and in the loose grazing system, namely the number of cattle sold and the cost of feed. The factor that has the most significant effect on cash income in both the tie system and the loose system is the number of cattle sold. Therefore, to increase the cash income of farmers, the number of livestock sold must be increased.